Design and development of integrated chassis of one seated urban car using embedded aluminium and FRP - Noor Akmal, Zolkifli (2010)
This thesis deals with propose of new design of urban concept car chassis which are to improve the existing design of chassis for Shell Eco Marathon Asia 2010, UMP SAE Team Urban Car Concept, Elaion Kratos. The existing design is analyzed to spot the value of chassis displacement due to driver and engine load. The chassis has to be strong enough with combination of good design and material used. The chassis will act as suspensions which absorb the load and vibration due to weight of driver and engine. Three designs are proposed to be compared with the previous one as the improvement in chassis displacement and weight of the chassis. In order to analyze the designs, wireframe model are built in FEMPRO software and the model are analyzed due to driver and engine load to see the displacement and weight of the new designs. The parameters that vary among the model are the design and parameters that vary the models with the existing chassis are the materials. Aluminium and fiberglass are used in new design as to improve the strength and weight of the chassis. Analyses are made and based on the simulation, the three design improve and succeeded and the best which is design 1 is applicable as replacement for the new chassis.